Modeling and experimental study on drying of apple slices in a convective cyclone dryer - Akpinar, EK; Bicer, Y; Midilli, A (Wiley, 2003)
The main objective pursued in this paper is to experimentally investigate the single layer drying behavior of apple slices in a convective type cyclone dryer and also to perform the mathematical modeling by using single layer drying models in literature. The experiments were conducted at drying air temperatures of 60, 70 and 80C in drying air velocities of 1 and 1.5 m/s. It was concluded that apple slices with the thickness of 12.5 mm would perfectly dry in the ranges of 280-540 min while those with the thickness of 8 mm would dry in the ranges of 180-320 min in these drying conditions by using convective type cyclone dryer. Additionally, the mathematical model describing the single layer drying curves was determined by nonlinear regression analysis, and the logarithmic model was selected as the most suitable model to obtain the drying curve equation of apple slices. Considering the parameters such as drying time, drying rate, moisture transfer, velocity and drying air temperature it is suggested that the apple slices be dried at the above optimum processing conditions.
Keywords: Hot-Air; Solar; Kinetics; Pistachio; Behavior; Potato